1994
DOI: 10.1029/94jc00531
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of capillary‐gravity wave spectra using a scanning laser slope gauge and microwave radars

Abstract: Capillary-gravity wave spectra are measured using a scanning laser slope gauge (SLSG), and simultaneously by X and K band Doppler radars off the Chemotaxis Dock at the Quissett campus of the Woods Hole Oceanographic Institution at Woods Hole, Massachusetts. Wave spectral densities estimated from the radar measurements using the Bragg theory agree with those measured using the SLSG at the Bragg wavenumber to within a few decibels, suggesting that Bragg scattering theory is valid for the conditions of this exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…In the experiment of Banner et al [37], their two-dimensional spectrum for short gravity waves shows a greater power spectral density at crosswind than alongwind. Hara et al [38] found that gravity waves (k = 49 rad/m) may exist and propagate against the wind from their observed spectra, and this can lead to a similar conclusion as Banner et al [37]. Further, the fitting procedure of the ∆ ratio showed negative values in the short gravity wavenumber range, which means that the energy of the spectrum in the crosswind direction can exceed the energy in the alongwind direction [28].…”
Section: An Improved Directional Spectrummentioning
confidence: 62%
See 1 more Smart Citation
“…In the experiment of Banner et al [37], their two-dimensional spectrum for short gravity waves shows a greater power spectral density at crosswind than alongwind. Hara et al [38] found that gravity waves (k = 49 rad/m) may exist and propagate against the wind from their observed spectra, and this can lead to a similar conclusion as Banner et al [37]. Further, the fitting procedure of the ∆ ratio showed negative values in the short gravity wavenumber range, which means that the energy of the spectrum in the crosswind direction can exceed the energy in the alongwind direction [28].…”
Section: An Improved Directional Spectrummentioning
confidence: 62%
“…Further, the fitting procedure of the ∆ ratio showed negative values in the short gravity wavenumber range, which means that the energy of the spectrum in the crosswind direction can exceed the energy in the alongwind direction [28]. There are no convincing physical explanations for this phenomenon [37,38]; however, some scholars have illustrated a number of kinetic characteristics of small-scale waves that can be instructive. Elfouhaily et al [21] demonstrated that a few of the shorter waves ridden on longer waves may travel perpendicular to the wind direction due to the interaction between wave.…”
Section: An Improved Directional Spectrummentioning
confidence: 99%
“…Instead, it experiences an accelerated roll-off at a rate exceeding the rates of both gravity and capillary spectra roll-offs. The accelerated roll-offcommences at wavenumbers which show no noticeable dependence on the wind energy input (Jfihne & Riemer 1990), although the influence of long waves appears to be important (Hara et al 1994). This behaviour finds a simple explanation in the framework of the present theory.…”
Section: Laboratorymentioning
confidence: 69%
“…(Jfihne & Riemer 1990) and field (Hwang et al 1993;Hara, Bock & Lyzenga 1994) observations showed that, contrary to intuitive expectations, the wavenumber spectrum in the capillary-gravity range does not exhibit a monotonic transition from the gravity wave to the capillary wave regime. Instead, it experiences an accelerated roll-off at a rate exceeding the rates of both gravity and capillary spectra roll-offs.…”
Section: Laboratorymentioning
confidence: 71%
“…A number of controlled experiments have been performed in wind-wave tanks under various set-ups, including those described in [66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Photographic Data Collectionsmentioning
confidence: 99%